Theoretical bases of Ciespal: the 1960s was a functionalist period? (Revista Internacional de Folkcomunicação, 2020)
This text brings a reflection about the thought that from 1960 to 1973 the International Center of Superior Communication Studies for Latin America has passed for a “functionalist period”. Based on bibliographic and documental research made on that center collection and on the study of the works by Émile Durkheim, Bronislaw Malinowski and Robert Merton, it was searched similarities and differences between the investigation indications that existed on Ciespal material on the 1960's and the functionalist doctrine. The study pointed that development communication has brought political proposals while the mass communication research (MCR) guided the scientific work, and that those two do not bring, necessarily, in their structures the functional way of thinking. Ciespal; Functionalism; Mass Communication Research.